PERAN VITAMIN D DALAM MENINGKATKAN PERFORMA ATLET - Ainun Jihaan Nauli Pulungan; Aurick Athallah Padraya; Fritzie Azalia Faustine; Irmayani Rahman; Reggina Maulidiana Tasya; Erica Kholinne (Jurnal Akta Trimedika, 2025)
Vitamin D is a micronutrient that plays a crucial role in maintaining bone health, muscle function, the immune system, and overall athletic performance. It helps strengthen bones, enhance muscle strength, support immunity, reduce injury risk, and accelerate recovery. Many athletes are reported to experience vitamin D deficiency, especially in regions with limited sunlight exposure. However, deficiency can also occur in tropical countries. In the body, vitamin D works through endocrine and autocrine mechanisms, with receptors distributed in almost all tissues, including skeletal muscles. Vitamin D increases calcium absorption in the intestines and maintains bone mineral balance, helping prevent stress fractures and accelerating tissue regeneration. In addition, vitamin D supports cardiovascular function, enhances the immune response, and strengthens type II muscle fibers, which are essential for strength and physical performance. Vitamin D supplementation can be beneficial for athletes, particularly those with deficiencies. Recommended doses range from 1,000 to 5,000 IU per day, depending on the individual’s vitamin D levels and the type of physical activity performed. Proper supplementation can reduce the risk of injury, speed up recovery, and improve physical endurance but must be done under supervision to prevent toxicity. Ensuring optimal vitamin D status is essential for the health and performance of athletes. Regular monitoring and personalized supplementation can help prevent deficiencies and maximize the benefits of vitamin D